(untitled) (CIPEEX, 2025)
With advances in medicine, there has been a reduction in premature mortality, leading to an increase in the world’s elderly population. Thus, it is known that aging brings about various deficits, making it necessary to take measures to improve quality of life, even with these changes present. Therefore, this study aims to evaluate the relationship between lower limb muscle strength (FM MMII), postural balance, and the occurrence of falls in elderly people with cognitive deficits. The study population consisted of 106 elderly individuals regularly enrolled at UniAPI, of whom only 60 met the inclusion criteria, among whom 34 elderly individuals had a lower score on the Mini Mental State Examination, presenting a reduction in cognitive level. Falls were observed through reports of falls in the last 12 months, while muscle strength was assessed using the sit-to-stand test and balance was assessed using a force platform using a variable from the Sway protocol. The study showed no relationship between cognitive level and the variables falls (p=0.865), balance (p=0.970 and p=0.882), and sit-to-stand test (muscle strength of lower limbs) (p=0.735), which were not statistically significant. However, further studies are needed, as this research was conducted in physically active older adults and the relationship between cognitive status and other variables may be altered in less active older adults.